Photic Zone Euxinia and Microbial Mat Development in the Early Triassic of the Perth Basin, Western Australia: Implications for Petroleum Systems - Taniwaki, Takashi (Curtin University, 2021)
Reconstruction of basin-scale paleogeography and paleoenvironments in the northern Perth Basin during the Early Triassic, utilising integrated geological and organic geochemical analyses, shows the distribution of photic zone euxinia and microbial mats following the end-Permian mass extinction. Such analyses also distinguish the organic geochemical signatures of photic zone euxinia and microbial mats, identify source rock potential across the basin, and have implications for the petroleum system in both the northern Perth and Northern Carnarvon basins.